Hubungan Status Gizi Ibu Pra Hamil Dengan Kejadian Weight Faltering Pada Bayi Usia 6-24 Bulan - Tasya Oktavia Wardani; Sugijati Sugijati; Nur Eva Aristina (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2026)
Weight faltering is a highly significant risk factor for malnutrition. The lower the Z-score, the higher the risk of malnutrition. One of the causes of stunted growth and development is maternal factors, specifically poor nutrition during the preconception period and pregnancy. This study aims to analyze the relationship between pre-pregnancy nutritional status and the incidence of weight faltering in infants aged 6-24 months. Research is an observational analytic study with a cross-sectional design. In this research used purposive sampling techniques on 50 infants aged 6-24 months who met the inclusion criteria in Selorejo village, Malang regency. The data were analyzed using the chi-square test. The Chi-Square correlation test analysis between pre-pregnancy nutritional status and the incidence of weight faltering in infants aged 6-24 months showed a significant relationship with a p-value of 0.002. There is a relationship between pre-pregnancy nutritional status and the incidence of weight faltering in infants aged 6-24 months. It is hoped that good preconception planning will be conducted before deciding to become pregnant again.